2022
DOI: 10.1101/2022.02.14.22270930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of antibody responses to two doses of ChAdOx1 nCoV-19 or BNT162b2 and a subsequent booster dose of BNT162b2 or mRNA-1273: population-based cohort study (COVIDENCE UK)

Abstract: SummaryBackgroundAntibody responses to SARS-CoV-2 vaccination vary for reasons that remain poorly understood.MethodsWe tested for presence of combined IgG, IgA and IgM (IgGAM) anti-spike antibodies before and after administration of two doses of ChAdOx1 nCoV-19 (ChAdOx1, Oxford-AstraZeneca) or BNT162b2 (Pfizer-BioNTech) in UK adults participating in a population-based longitudinal study who received their first dose of vaccine from December 15, 2020 to July 10, 2021. Information on sixty-six potential sociodem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
1
12
1
Order By: Relevance
“…By contrast with studies showing that a longer inter-dose interval increases immunogenicity, 21,34,35 we found a strong association between longer interval between first and second vaccine doses and increased risk of breakthrough infection. While a correlate of protection that translates immunogenicity findings into real-world protection has yet to be found, some preliminary studies suggest a longer interval is indeed protective.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…By contrast with studies showing that a longer inter-dose interval increases immunogenicity, 21,34,35 we found a strong association between longer interval between first and second vaccine doses and increased risk of breakthrough infection. While a correlate of protection that translates immunogenicity findings into real-world protection has yet to be found, some preliminary studies suggest a longer interval is indeed protective.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, after a booster vaccination, we observed lower risk of breakthrough infection for participants of south Asian or mixed ethnicity compared with White participants after adjusting for previous infection. This supports both pre-vaccination and post-vaccination serology findings from the same cohort, showing higher antibody titres from natural infection and from vaccination in these ethnic groups than in White participants, independently of pre-vaccination serostatus 21 and disease severity. 19 Few studies to date have observed associations between ethnicity and breakthrough SARS-CoV-2 infection, 14 although lack of diversity in vaccine clinical trials 25 and missing data in some of the larger observational studies 2,9 have hindered investigation.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…7,9 Participants of Asian/Asian British origin also had higher convalescent titres of combined IgG, IgA and IgM antibodies to the SARS-CoV-2 spike protein following infection (after adjustment for multiple potential confounders including disease severity) and higher titres of the same antibodies after SARS-CoV-2 vaccination (after adjustment for multiple potential confounders including pre-vaccination anti-S titres). 9,10 Taken together, these findings highlight the need to investigate potential biological determinants of ethnic variation in susceptibility to, and severity of, COVID-19.…”
Section: Resultsmentioning
confidence: 88%